IMPLEMENTATION OF THE MIND MAPPING MODEL WITH SCATTERGORIES GAME IN IMPROVING CREATIVITY AND LEARNING OUTCOMES IN NATIONAL EDUCATION MATERIALS (Journal of Humanities and Social Studies, 2018)
This study aims to find the Application of the Mind Mapping Model with Game Scatterories in Improving Student Creativity and Learning Outcomes in the Indonesian Legislation Regulations Material in class VI of MI Nurul Huda Cimanggis Depok. The results obtained were the Application of the Mind Mapping Model with Game Scattergories, the first cycle by obtaining an average score of 69.22, in the second cycle a score of 74.18 was obtained and in the third cycle the Application of the Mind Mapping Model with Game Scattergories managed to score 77 , 90 points and succeeded in increasing the Learning Outcomes variable in National Legislation Materials and Creativity in achieving student completeness. The conclusion of the study is the Application of the Mind Mapping Model with Game Scatterories has succeeded in improving Learning Outcomes in the Material of National Legislation Regulations and Creativity of Grade VI MI Nurul Huda Cimanggis Depok. The implication of the research is to make the results of research as a reference in developing students' creativity and the concept of national legislation can be used as a guide for behavior in life in families, schools and communities. Suggestions are intended for students, teachers, principals, governments, institutions and students so that the results of this study can be a reference in the development of learning models.